Cross-Cultural Adaptation and Psychometric Evaluation of the Herth Hope Index Within a Sample of Iranian Older Peoples. (December 2019) - Yaghoobzadeh, Ameneh; Pahlevan Sharif, Saeed; Ong, Fon Sim; Soundy, Andrew; Sharif Nia, Hamid; Moradi Bagloee, Mohammad; Sarabi, Mahnaz; Goudarzian, Amir Hossein; Morshedi, Hadi
There is a need to better understand the measurement of hope within a variety of cross-cultural contexts and older population. The objective of this study was to examine the psychometric characteristics of the Persian translation of the Herth Hope Index (HHI-Persian). This study used a sample of 500 Iranian older people in Iran. Psychometric properties of the HHI-Persian were evaluated using face, content, and construct validity. The construct validity of the instrument was tested using exploratory and confirmatory factor analysis. Reliability assessed is within the acceptable range. Construct validity of the scale showed two factors explaining 49.22% of the variance. Internal consistency of 12 items was greater than .70. The HHI-Persian is a short, reliable, and valid assessment scale of hope in older people. The article ends with suggestions for further research.